Organic farming and fair trade approach: the experience of Italian Association for Organic Agriculture (AIAB) – the case of Umbria. (2017) - Ascani, Michela; Cecchini, Lucio; Pedini, Sergio
There is a strong growth of organic and fair trade movements and in both cases, the rules have incorporated new components following the society's expectations. Direct market local experiments in which the movements approach towards criteria and determinations that tend to have an equalised relation have been taking place. This study regards the experience of GODO – Solidarity Purchase Group in Umbria Region (Italy), with the aim of investigating the behaviour and the main characteristics of both consumers and farmers GODOs members, always related to organic and fair trade aspects, considering consumers and farmers differences. The results point out that the short-chain marketing experience is a real example of the fact that it is absolutely possible and feasible to have a new approach between the two movements, but the research showed that this is not true to all kinds of consumers and farmers.